Common tumour, uncommon presentation: massive lipoma in the retroperitoneum. Issue 1 (January 2018) - Govindarajan, Krishna Kumar; Sreepathy, Shiju K.; Badhe, Bhawana; Ananthakrishnan, Ramesh
Abstract : Retroperitoneal masses are notoriously malignant. Although they are seen commonly in adults, they have been known to occur in children as well. A benign mass in the retroperitoneal location in children is uncommon. Here we describe the presentation and management of a rare benign retroperitoneal mass in a 12-year-old boy.